The Effect of Manual Therapy on the Adolescent Idiopathic Scoliosis in a 28 Years Old Woman - Marzieh Mohamadi; Farahnaz Ghaffari-Nejhad (University of Social Welfare and Rehabilitation Sciences, 2013)
Idiopathic scoliosis (IS) is the most common type of scoliosis. Clinical signs and symptoms of scoliosis impair quality of life and daily function. Manual therapy is commonly used for treatment of scoliosis. This is a case report of scoliosis treatment with manual therapy in a 28 years old patient. A 28 years old woman complained of low back pain for 4 years. Spine x-ray, showed scoliosis with a 32 degrees Cobb angle. The patient received a manual therapy procedure of two visits per week for 16 weeks including myofascial release technique, mobilization and manipulation. The Cobb angle was reduced 15.62% after 8 weeks and 21.87% after 16 weeks. In addition the pain was reduced by 50%. We can state that manual therapy was useful for this patient.